Hubungan antara ukuran tubuh dan bobot badan pada induk sapi perah Friesian Holstein laktasi pertama - Rizki Amalia Nurfitriani; Adirangga Fahrudin; Hafidz Ilyas At Thariq; Mochamad Alfinanda Santriagung; Erlangga Satria Mulyadi Putra; Nurkholis; Hariadi Subagja; Erfan Kustiawan; Aan Awaludin; M Adhyatma (Universitas Sulawesi Barat, 2021)
This study aims to determine the relationship between body size and bodyweight of the first lactating FH dairy cow. The research method used was linear regression analysis with 17 individuals at 27-29 months. The observed variables were body weight (BW), body length (BL), shoulder height (SH), and chest circumference (CC). The results showed that the correlation value between BW and BL was 0.6791 with the correlation regression equation Y = -724.63+7.68X1. SH and BW have a correlation value of 0.4043. CC with BW has a correlation value of 0.6863 with the regression equation Y = -733.455.90X1. The relationship between BL and SH has a correlation value of 0.2048. BL and CC have a correlation value of 0.4832. The conclusion of this study was that BW has a correlation of 67.91% to BL and 68.63% to CC of first lactating dairy cows, but does not have a correlation to SH. The more the BL and CC of the first lactating dairy cow increased, the more the weight of the dairy cow increased. BL does not have a correlation with SH and CC. SH has a 60.08% correlation with CC.